2022
DOI: 10.3390/sym14010091
|View full text |Cite
|
Sign up to set email alerts
|

Time-like Proton Form Factors with Initial State Radiation Technique

Abstract: Electromagnetic form factors are fundamental quantities describing the internal structure of hadrons. They can be measured with scattering processes in the space-like region and annihilation processes in the time-like region. The two regions are connected by crossing symmetry. The measurements of the proton electromagnetic form factors in the time-like region using the initial state radiation technique are reviewed. Recent experimental studies have shown that initial state radiation processes at high luminosit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The experimental values of the proton effective FF (time-like region) [11,12], obtained by various collaborations, are shown in Figure 3. Recently, the BESIII Collaboration studied the process e + e − → pp(γ) [13], using both procedures of the energy scan from √ s = 2.00 GeV up to √ s = 3.08 GeV and the initial state radiation.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental values of the proton effective FF (time-like region) [11,12], obtained by various collaborations, are shown in Figure 3. Recently, the BESIII Collaboration studied the process e + e − → pp(γ) [13], using both procedures of the energy scan from √ s = 2.00 GeV up to √ s = 3.08 GeV and the initial state radiation.…”
Section: Resultsmentioning
confidence: 99%
“…energy of the collider is systematically varied. Within this paper, only former results, as well as future experiments employing the scan method, are reviewed, whereas an overview of results with the ISR method can be found in [15]. Further reviews about nucleon EM FFs in the TL region in general and other baryon FFs can be found in [16] and [17], respectively.…”
Section: Scan Methodsmentioning
confidence: 99%
“…where c 0 is the same parameter as in Equation (15) and is determined to be c 0 = 5.61 +1.37 −1.33 GeV 2 from the TL-SL joint fit. [36,37,45,46], BABAR [47][48][49], CMD3 [34,35], BES [32], FENICE+DM2 [20][21][22]24,25,41], E835 [30,31], and PS170 [26][27][28] and in the spacelike region from the GEp Collaboration [58].…”
Section: Theoretical Estimates Of the Proton Radiusmentioning
confidence: 99%
“…TL EM FFs are complex functions of four momentum transfer and can be acossiated with the time evolution of the electric charge and magnetization within the nucleon [12]. Reviews of the results can be found in [13,14]. The neutron on the other hand still remains a mystery due to experimental difficulty of detecting a neutral hadron and unavailibility of an anti-neutron beam.…”
Section: Introductionmentioning
confidence: 99%